(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Banks face many of the various risks: which are of dangerous phenomena that cause the state achieved a waste of money and a threat to future development plans to be applied to reach the goals set by: prompting banks and departments to find appropriate solutions and fast: and it was within these solutions rely on Banking risk management and effective role in defining and identifying: measuring and monitoring risk and trying to control and take risks is expected to occur in order to encircle and make it in within acceptable limits: and try to avoid them in the future to reduce the losses that are likely to be exposed to the bank: and it began to emerge and dominate a lot of legislation that seeks to structure the year risk management and the development of specific frameworks for risk all kinds: scope and develop appropriate solutions to control it and reduced to the minimum: and under the supervision of senior management that works to provide all disciplines qualified scientifically and practically: and that the success of risk management depends on the extent of his commitment to legislation and frameworks specific and clear objectives and the extent of early preparedness to reduce risks: as well as the case of the external auditor through audit procedures and according to the method of risk in accordance with the decisions of the Basel (||): and that the research problem is the limited use of indicators to measure bank risk by external auditors when performing audit procedures in the banking sector: and the research aims in general to emphasize the importance and the role of the external auditor to protect the banks from the banking risks: continuity and highlight the legislation and the recommendations of the Basel Committee (||) in the development of standards and uniform rules to adjust the performance of the banking business: and the importance of research showing through the process of consistency and application of international standards and modern concepts of the decisions of the Commission international Basel with current applications in local banks in the management of banking risks: as well as the contribution of research in Motion program of testing and scrutiny on risk management in the banking sector in the light of international standards and recommendations of the Basel (||) and domestic legislation. And was based on research on the basic premise that the adoption of the external auditor on the international auditing standards and recommendations of the Basel (||) leads to increase the effectiveness of the audit on the management of banking risks in order to achieve the desired goals of this research and give a better perception of the reader and are streamlined and logical: they have adopted a researcher two methods represent the first to provide a theoretical study on the subject by outsourcing scientific academic related material research: while the second method has been focused on field research in what has been presented in the theoretical side of concepts through the application of a prototypical tests of controls and risk assessment of banking in the light of theoretical study and practical has been reached to a set of conclusions and recommendations on the subject of search and appointed selected.